Ethylene-regulated asymmetric growth of the petal base promotes flower opening in rose (Rosa hybrida). Issue 4 (2nd February 2021) - Cheng, Chenxia; Yu, Qin; Wang, Yaru; Wang, Hong; Dong, Yuhan; Ji, Yuqi; Zhou, Xiaofeng; Li, Yonghong; Jiang, Cai-Zhong; Gan, Su-Sheng; Zhao, Liangjun; Fei, Zhangjun; et al.
Abstract: Flowers are the core reproductive structures and key distinguishing features of angiosperms. Flower opening to expose stamens and gynoecia is important in cases where pollinators much be attracted to promote cross-pollination, which can enhance reproductive success and species preservation. The floral opening process is accompanied by the coordinated movement of various floral organs, particularly petals. However, the mechanisms underlying petal movement and flower opening are not well understood. Here, we integrated anatomical, physiological, and molecular approaches to determine the petal movement regulatory network using rose ( Rosa hybrida ) as a model. We found that PETAL MOVEMENT-RELATED PROTEIN1 ( RhPMP1 ), a homeodomain transcription factor (TF) gene, is a direct target of ETHYLENE INSENSITIVE3, a TF that functions downstream of ethylene signaling. Rh PMP1 expression was upregulated by ethylene and specifically activated endoreduplication of parenchyma cells on the adaxial side of the petal (ADSP) base by inducing the expression of Rh APC3b, a gene encoding the core subunit of the Anaphase-Promoting Complex. Cell expansion of the parenchyma on the ADSP base was subsequently enhanced, thus resulting in asymmetric growth of the petal base, leading to the typical epinastic movement of petals and flower opening. These findings provide insights into the pathway regulating petal movement and associated flower-opening mechanisms. Abstract : Ethylene controls endoreduplication, thus influencing asymmetric growth of petal bases via a regulatory cascade involving RhEIN3-RhPMP1-RhAPC3b to promote petal movement and flower opening in rose.